Postdate Pregnancy Maternal and Fetal Outcomes among Sudanese Women - Suliman, Awadalla Abdelwahid; Abdelrahman, Gawahir Murad; Ahmed, Hajar Suliman Ibrahim; Ibrahim, Abdelgadir Suliman; Hammad, Kabbashi Mohammed Adam; Omer, Emad Abdalla Siddig; Handady, Siddig Omer M (Clinical Journal of Obstetrics and Gynecology, 2023)
Background: Postdated pregnancy is one of the most common obstetric problems associated with increased maternal morbidity, prenatal morbidity, and mortality. Pregnancy at 37-40 weeks of gestation is called the term from the last menstrual period. If the pregnancy exceeds 40 weeks, it is called a postdated pregnancy, but when pregnancy is prolonged beyond 42 weeks, it is called post-maturity or post-term pregnancy. Objective: This study aimed to determine the adverse effects of postdate pregnancy on mothers and fetuses. Methodology: This was a descriptive, prospective, cross-sectional, hospital-based study conducted at Omdurman Maternity Hospital from January 2018 to June 2018. An interview questionnaire was used to collect data. Data were collected by trained doctors in the labor room. One hundred and thirty-eight (138) postdated pregnant women were included in this study after obtaining informed consent through a structured questionnaire. Demographic and clinical data concerning personal history, booking status, mode of delivery, maternal complications, and fetal complications were recorded. Results: During the study period, 2751 women delivered, of which 138 were postdated deliveries, with a prevalence of 5%. Most women's age range was 31-34 years 48.6%). Their education level was mostly secondary school (42%). Primigravida 65%), booked were 75.4%. Previous history of postdate pregnancy was 34.1%, normal vaginal delivery was 79 .7%, cesarean section was 14.5%, and instrumental delivery 5.8%. Cesarean section indications were cervical dystocia (14.4%), cephalopelvic disproportion (9.5%), meconium-stained liquor with fetal distress (33.3%), pathological cardiotocography (CTC) (19%), and failure to progress (23.8%). Maternal complications included post-partum hemorrhage (PPH) (7.2%), perineal tears (.7%, cervical tears (1.4%), and postpartum infections (1.4%). Fetal complications were 14.5%, Shoulder Dystocia 2.9%, asphyxia (6.5%), and meconium aspiration (5.1%). The mean APGAR score was 1.1667, less than three in only 3.6%, and > 7 in 86.9%. Neonatal death was 3%. Approximately 18 neonates were admitted to the Neonatal Intensive care unit (NICU) and only five of them were admitted for more than one week. Conclusion: Postdate pregnancy prevalence in this study was 5%, which was associated with maternal risk of cesarean section delivery, instrumental delivery, postpartum hemorrhage, and postnatal infection.